Landscape and Politics on the Olympic Peninsula: Social Agendas and Contested Practices in Scientific Forestry - Alx Dark (Journal of Political Ecology, 1997)
Land managers have recently shifted scientific practice and management discourse to depoliticize and suppress social conflicts over the environment. The transformation of the landscape of the Olympic Peninsula, particularly the logging of old-growth forests, has involved residents in challenging these developments, reordering the landscape to create contradictory, cultural claims to the future of the peninsula and its resources.